The Diversity of Biosimilar Design and Development: Implications for Policies and Stakeholders - Grampp, Gustavo (BioDrugs, 2015)
Biosimilars are required to be similar or highly similar in structure to their biologic reference product but are neither expected nor required to contain identical active substances. For example, glycosylated biosimilars approved to date demonstrate quantitative and qualitative structural differences from their reference product and exemplify the latitude of variations permitted for biosimilars. Although differences between a candidate biosimilar and its reference product will be evaluated for differential clinical effects during biosimilarity assessment, it is unlikely that potential differences between any two indirectly related biosimilars will be formally evaluated. Furthermore, biosimilar pathways permit variations in pharmaceutical attributes, clinical development approaches, and regulatory outcomes, resulting in further diversity of attributes among approved biosimilars. Because biosimilars may vary across the ranges of structural and functional acceptance criteria, they should not be treated like multisource, generic drugs.